Disease Trends in Appendix in Relation to Age, Gender and Month of the Year (Medical Forum Monthly, 2024)
Background: Appendicectomy specimens received with suspected acute appendicitis often macroscopically appear normal in size, shape etc but a more menacing underlying pathology can be found in histopathological analysis of these cases. Worldwide appendicitis is a commonly found condition in children and adults but cancers of the appendix are very rare. Most of them are found accidentally on appendectomies performed for appendicitis.Study Design: Cross sectional study.Place and Duration of Study: This study was conducted at Dow diagnostic research and referral laboratory, DDRRL, OJHA campus Karachi from January 2011 till December 2011.Materials and Methods: We evaluated Histopathology reports of all appendicectomy specimens received at the Dow Lab, Ojha campus, Karachi for the past one year. Data analyses focused on confirmation of acute appendicitis, incidental unexpected findings and whether these unexpected findings can affect the management of patient. Also to assess the pattern of variation with age, sex, and seasons of the year. We also have tabulated each appendectomy by month and season of its occurrence. Analyses are done on SPSS version 16. Descriptives and cross tabs are used.Results: The histopathology reports disclose a variety of hyperplasic and malignant incidental lesions besides different acute inflammatory conditions. Among the total 414 cases, 77 cases (18.5%) are hyperplasic conditions, 329 cases (79.4%) are acute inflammatory condition 5 cases (1.2%) are parasitic infestation and 3 cases (0.72%) are cancers. Males are affected more commonly then females with a ratio of 2.1:1. Most commonly children are involved with the hyperplasic appendix lesions while adults with peak incidence in the 13-40 years of age are involved in acute inflammatory conditions. Carcinomas occur in the later ages. Incidence is higher in the months of February, March, April, May and September.Conclusion: Findings in the appendix lesions consist of hyperplasic, inflammatory conditions, parasitic infestation and tumors. Lesions are most common in the summer and spring seasons. Three cases (0.72%) of appendiceal tumors are found which affect the outcome of patient management. Results of our study show that in addition to the operative findings, the routine histopathological examination of the appendix yields important clinical information also so it should be undertaken in all cases.